A Systematic Review of the Complications Associated with Free Fibular Flaps in Adult and Pediatric Spinal Reconstruction - Zhu, Katherine J.; Cho, Annie M.; Beckett, Joel S.; Macyszyn, Luke; Mathes, David; Nguyen, Phuong; Irwin, Timothy; Kaouzanis, Christodoulos; Yu, Jason W. (Journal of Reconstructive Microsurgery, 2024)
Background Free fibular flaps have been suggested as a modality of reconstruction for complex spinal deformities. However, there is limited data that describes associated postoperative outcomes. The purpose of this systematic review was to characterize outcomes after spinal reconstruction using the free fibular flap for both adults and children.Methods Thirty-nine articles among four databases were identified as having met inclusion criteria. Patient demographics, indications for spinal reconstruction as well as location and anastomosis, history of chemotherapy and radiation therapy, and postoperative outcomes including complications were identified. Major complications were defined as complications requiring reoperation, while minor complications were those that did not require reoperation. Systemic complications were defined as complications affecting sites or organ systems beyond the local donor and recipient sites. Statistical analysis was performed using Fischer's exact, chi-squared, and t-tests.Results We identified 218 adult patients (mean age 47.7 years, 56.4% male) and 27 pediatric patients (mean age 12.7 years, 55.6% male). While there was no significant difference in the rates of bony union between the two groups (adults: 90.8%, children: 90%, p > 0.9), adults had significantly higher rates of major (27% vs. 7.4%, p = 0.026), minor (26.1% vs. 7.4%, p = 0.032), and systemic (14.2% vs. 0%, p = 0.047) complications.Conclusion Free fibular flaps are effective for spinal reconstruction for both adults and children, as evidenced by the high rates of bony union. However, adults exhibited significantly higher complication rates. Further research is required to better understand the patient and clinical risk factors associated with increased rate of complications.
Keywords: free fibular flap; vascularized fibular graft; spinal reconstruction; systematic review